Pemberdayaan Kelompok Sadar Wisata Desa Enu Melalui Pelatihan Pembuatan Souvenir dari Batu Alam dan Kelapa - Ramadhani, Sriyati; Ramlan, Ratnasari; Bidin, Cici Rianty K (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
This Community Service Program was implemented in Enu Village, Sindue Subdistrict, Donggala Regency, with the objective of empowering the Tourism Awareness Group (Pokdarwis) through training in souvenir production based on local resources, namely natural stone and coconut shells. The program was designed to enhance community technical skills in producing value-added products, strengthen Pokdarwis institutional management, and encourage social participation in the development of village-based tourism. A participatory approach was applied, encompassing program socialization, training in souvenir production skills, finishing and packaging techniques, simple marketing strategies, basic financial bookkeeping, as well as the preparation of standard operating procedures (SOPs) and organizational structures. The results indicate a significant improvement in Pokdarwis members’ ability to produce various types of simple souvenirs made from natural stone and coconut shells, including keychains, wall decorations, and table ornaments. From an institutional perspective, Pokdarwis has implemented basic bookkeeping practices, developed SOPs, and established an organizational structure as a foundation for more professional and sustainable group management. In terms of social outcomes, the program promoted active involvement of youth, women’s groups, and local micro, small, and medium enterprises (MSMEs), contributing to strengthened social cohesion and collective awareness in managing village potential. Overall, this PKM program successfully enhanced production capacity, reinforced Pokdarwis institutional management, and supported the development of an inclusive and competitive creative economy ecosystem based on village tourism as part of a sustainable rural development strategy. Keywords: Community empowerment, tourism awareness group, natural stone souvenirs, coconut shell souvenirs, village tourism. Program Pengabdian kepada Masyarakat (PKM) ini dilaksanakan di Desa Enu, Kecamatan Sindue, Kabupaten Donggala, dengan tujuan memberdayakan Kelompok Sadar Wisata (Pokdarwis) melalui pelatihan pembuatan souvenir berbasis potensi lokal berupa batu alam dan kelapa. Kegiatan ini dirancang untuk meningkatkan keterampilan teknis masyarakat dalam menghasilkan produk bernilai tambah, memperkuat manajemen kelembagaan Pokdarwis, serta mendorong partisipasi sosial masyarakat dalam pengembangan desa wisata. Metode pelaksanaan menggunakan pendekatan partisipatif yang meliputi sosialisasi program, pelatihan keterampilan produksi souvenir, teknik finishing dan pengemasan, strategi pemasaran sederhana, pembukuan usaha, serta penyusunan standar operasional prosedur (SOP) dan struktur organisasi. Hasil kegiatan menunjukkan adanya peningkatan kemampuan anggota Pokdarwis dalam memproduksi berbagai jenis souvenir sederhana berbahan batu alam dan kelapa, seperti gantungan kunci, hiasan dinding, dan pajangan meja. Dari aspek kelembagaan, Pokdarwis telah menerapkan pembukuan sederhana, menyusun SOP, serta membentuk struktur organisasi sebagai dasar pengelolaan kelompok yang lebih profesional dan berkelanjutan. Pada aspek sosial, program ini mendorong keterlibatan aktif pemuda, kelompok perempuan, dan pelaku UMKM lokal, yang berkontribusi pada penguatan kohesi sosial dan kesadaran kolektif dalam mengelola potensi desa. Secara keseluruhan, program PKM ini berhasil meningkatkan kapasitas produksi, memperkuat manajemen kelembagaan Pokdarwis, serta membangun ekosistem ekonomi kreatif berbasis desa wisata yang inklusif dan berdaya saing sebagai bagian dari strategi pembangunan desa yang berkelanjutan. Kata Kunci: Pemberdayaan masyarakat, pokdarwis, souvenir batu alam, souvenir kelapa, desa wisata.